Using Teaching Proficiency Through Reading and Storytelling (TPRS) in Teaching English for Young Learners - Arini Octaviani; Vega Hesmatantya (Tell : Teaching of English Language and Literature Journal, 2018)
This study was conducted in order to find out how to improve students’ skills in retelling at kindergarten students of JAC School Surabaya. It described the implementation of Using Teaching Proficiency through Reading and Storytelling (TPRS) in teaching learning process and reported students’ retelling story ability. This research used Classroom Action Research (CAR) which is conducted to solve the students’ during story telling time and students’ ability in retelling story. The study uses Burns theory. This Classroom Action Research has four steps in one cycle. Those are planning, acting, observing, and reflecting. The writer used a descriptive qualitative design to gain the information concerning process of TPRS method. There are three steps of TPRS teaching method. Those are Established the Meaning, Tell a class story and Read. There was an activity called circling in tell a class story step According to the data, the students made an improvement of retelling story use their own language from the first to the second cycle. The average of students score in retelling story rubric of the first cycle was 2 as described as fair category. While the second cycle average of retelling story rubric was 4 and categorized as excellent. The data was the result of direct observation. The analysis was done by describing the implementation of using TPRS in learning process in the classroom.